2017
DOI: 10.1128/jb.00527-16
|View full text |Cite
|
Sign up to set email alerts
|

EssE Promotes Staphylococcus aureus ESS-Dependent Protein Secretion To Modify Host Immune Responses during Infection

Abstract: Staphylococcus aureus, an invasive pathogen of humans and animals, requires a specialized ESS pathway to secrete proteins (EsxA, EsxB, EsxC, and EsxD) during infection. Expression of ess genes is required for S. aureus establishment of persistent abscess lesions following bloodstream infection; however, the mechanisms whereby effectors of the ESS pathway implement their virulence strategies were heretofore not known. Here, we show that EssE forms a complex with other members of the ESS secretion pathway and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 61 publications
3
34
0
2
Order By: Relevance
“…Despite the ess locus forming part of the core S. aureus genome, these four substrate proteins are not conserved across S. aureus isolates, being found in only approximately 50% of sequenced strains 19 . Furthermore, inactivation of the T7SS in S. aureus strain ST398 shows a similar decrease in kidney abscess formation as that seen for T7 mutants in Newman and USA300 2, 4, 20 , despite the fact that recognizable homologues of EsxB/EsxC/EsxD/EsaD are not encoded by this strain 19 . This strongly suggests that there are further S. aureus T7 substrates that are yet to be identified.…”
Section: Introductionmentioning
confidence: 51%
“…Despite the ess locus forming part of the core S. aureus genome, these four substrate proteins are not conserved across S. aureus isolates, being found in only approximately 50% of sequenced strains 19 . Furthermore, inactivation of the T7SS in S. aureus strain ST398 shows a similar decrease in kidney abscess formation as that seen for T7 mutants in Newman and USA300 2, 4, 20 , despite the fact that recognizable homologues of EsxB/EsxC/EsxD/EsaD are not encoded by this strain 19 . This strongly suggests that there are further S. aureus T7 substrates that are yet to be identified.…”
Section: Introductionmentioning
confidence: 51%
“…Данный интерлейкин функционирует как провоспалительный цитокин, который вызывает два основных эффекта: способ-ствует рекрутированию CD4 + Т-лимфоцитов, преи-мущественно Th 1 -клеток, и ингибирует Тh 2 -клетки. Также IL-16 индуцирует хемотаксис эозинофилов и дендритных клеток [3,63].…”
Section: Il-16unclassified
“…Во время заболеваний, вызванных Staphylococcus aureus, наблюдается повышение экспрессии IL-12, который вместе с IL-17 играет доминиру-ющую роль в патогенезе стафилококковой ин-фекции [3,79]. Quang- Tam В то же время существуют данные, что IL-12 способствует стафилококковой колонизации [106] и препятствует благоприятному течению Staphylococcus aureus-индуцированного абсцес-са головного мозга [40], а назначение препаратов биологической терапии (в частности, устекину-маба), подавляющих активность IL-12, пациентам с неконтролируемым воспалением, вызванным Staphylococcus aureus, приводит к выздоровлению пациентов [49].…”
Section: Il-12unclassified
“…aureus EssD nuclease activity affects IL-12 signaling during bloodstream infection. Anderson et al reported that the surge of IL-12 cytokine signaling associated with S. aureus bloodstream infection in mice requires EssE-mediated secretion of ESS pathway effectors (25). We wondered whether the EssD nuclease activity of S. aureus USA300 is also required for the induction of IL-12 signaling.…”
Section: Fig 7 Expression Of Essd Does Not Confer Any Growth Advantagmentioning
confidence: 99%
“…In S. aureus, the ESS pathway contributes to the stimulation of IL-12 (p40) and IL-12 (p35) production and secretion during mouse infection (25). This immunomodulatory activity is thought to contribute to S. aureus virulence and persistence within deepseated abscess lesions (7,26).…”
Section: Importancementioning
confidence: 99%